The Clinical Utility of the MOCA in iNPH Assessment - Wesner, Eric; Etzkorn, Lacey; Bakre, Shivani; Chen, Jinyu; Davis, Alexander; Zhang, Yifan; Yasar, Sevil; Rao, Aruna; Luciano, Mark; Wang, Jiangxia; Moghekar, Abhay (Frontiers in Neurology, 2022)
Objectives We sought to estimate reliable change thresholds for the Montreal Cognitive Assessment (MoCA) for older adults with suspected Idiopathic Normal Pressure Hydrocephalus (iNPH). Furthermore, we aimed to determine the likelihood that shunted patients will demonstrate significant improvement on the MoCA, and to identify possible predictors of this improvement. Methods Patients (N = 224) presenting with symptoms of iNPH were given a MoCA assessment at their first clinic visit, and also before and after tap test (TT) or extended lumbar drainage (ELD). Patients who were determined to be good candidates for shunts (N = 71, 31.7%) took another MoCA assessment following shunt insertion. Reliable change thresholds for MoCA were derived using baseline visit to pre-TT/ELD assessment using nine different methodologies. Baseline characteristics of patients whose post-shunt MoCA did and did not exceed the reliable change threshold were compared. Results All nine of reliable change methods indicated that a 5-point increase in MoCA would be reliable for patients with a baseline MoCA from 16 to 22 (38.4% of patients). Furthermore, a majority of reliable change methods indicated that a 5-point increase in MoCA would be reliable for patients with a baseline MoCA from 14 to 25. Reliable change thresholds varied across methods from 4 to 7 points for patients outside of this range. 10.1% had at least a 5-point increase from baseline to post-TT/ELD. Compared to patients who did not receive a shunt, patients who received a shunt did not have lower average MoCA at baseline (p = 0.88) or have better improvement in MoCA scores after the tap test (p = 0.17). Among shunted patients, 23.4% improved by at least 5 points on the MoCA from baseline to post-shunt. Time since onset of memory problems and post-TT/ELD gait function were the only clinical factors significantly associated with having a reliable change in MoCA after shunt insertion (p = 0.019; p = 0.03, respectively). Conclusions In patients with iNPH, clinicians could consider using a threshold of 5 points for determining whether iNPH-symptomatic patients have experienced cognitive benefits from cerebrospinal fluid drainage at an individual level. However, a reliable change cannot be detected for patients with a baseline MoCA of 26 or greater, necessitating a different cognitive assessment tool for these patients.